Foster care in the new legal framework. New speeches, new practices? - Delgado, Paulo (2018)
The Children and Young People in Danger Protection Act, updated by Law No. 142/2015, introduces significant changes in the foster and residential care system, for children and young people. This work develops an explanatory and critical analysis of the new legal provisions, evaluating their suitability to reduce the institutionalization of children removed from their parents, in favour of an alternative family environment. It has been concluded that legal changes, even if they are overall positive, will have good results only when combined with strategies that inform, support, and fund foster care in a fair way. The necessary procedures in the selection and training of new foster families should be adopted immediately.